Larvicidal and histopathological efficacy of cinnamic acid analogues: a novel strategy to reduce the dengue vector competence. Issue 16 (29th March 2022) - Naresh, P.; Rajesh Kumar, R.; Vishwas, H. N.; Rajagopal, Gopalan; Prabha, T.; Jubie, S.
Abstract : Cinnamic acid analogues as potent compounds for controlling Aedes aegypti in biological way. Abstract : Background : A novel strategy such as conjugation of amino, Schiff's bases, and thiadiazole moieties to the cinnamic acid nucleus has been adopted in this study to discover new molecules that target the dengue envelope protein (DENVE). Aim : Among the different domains of dengue virus envelope protein (PDB ID ; 1OKE ), we have selected a ligand-binding domain for our structure-based drug design. The designed compounds have also been docked against DENVE protein. Methodology : Based on the in silico results and synthetic feasibility, three different schemes were used to synthesize twenty-three novel cinnamic acid derivatives. Sci-finder ascertained their novelty. The synthesized derivatives were consistent with their assigned spectra. The compounds were further evaluated for their larvicidal activity and histopathological analysis. Multiple linear regression analysis was performed to derive the QSAR model, which was further evaluated internally and externally for the prediction of activity. Results and discussion: Four compounds, namely CA 2, CA 14, ACA 4, and CATD 2, effectively showed larvicidal activity after 24, 48, and 72 h exposure; particularly, compound CA2 showed potent larvicidal activity with LC50 of 82.15 μg ml −1, 65.34 μg ml −1, and 38.68 μg ml −1, respectively, whereas intermittent stages, causes of abscess in the gut, and siphon regions were observed through histopathological studies. Conclusion : Our study identified some novel chemical scaffolds as effective DENVE inhibitors with efficacious anticipated pharmacokinetic profiles, which can be modified further.